Spiritual Mindfulness Berbasis Adaptation Theory terhadap Kecemasan dan Vital Sign pada Pasien Pneumonia - Dessy Era Puspitasari; Ninuk Dian Kurniawati; Moecharom Moecharom; Daviq Ayatulloh; Diah Priyantini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of spiritual mindfulness based on adaptation theory on anxiety and vital signs in pneumonia patients. The research method uses a quasi-experiment in pneumonia patients at RSUD Dr. Soetomo, Surabaya. Forty-eight respondents were divided into 24 intervention groups and 24 control groups recruited using purposive sampling. The independent variable is spiritual mindfulness based on adaptation theory. The dependent variable is anxiety, measured using the Zung SRAS questionnaire, and vital signs are measured using observational data. Data analysis using Paired t-test and independent t-test. The study results in the intervention group showed a significant effect of the intervention on anxiety (p=0.000; d=1.436) and vital signs (systolic blood pressure p=0.000, diastolic blood pressure p=0.001, pulse p=0.000, respiratory rate p=0.000 and SPO2 p = 0.001. In conclusion, spiritual mindfulness techniques based on adaptation theory can reduce anxiety and vital signs of pneumonia patients at Dr. Soetomo Hospital, Surabaya. Keywords: Anxiety, Mindfulness, Pneumonia, Spirituality, Vital Sign